Relationships of Serum Bone Turnover Markers With Metabolic Syndrome Components and Carotid Atherosclerosis in Patients With Type 2 Diabetes Mellitus - Li, Wei; Liu, Xiaojun; Liu, Lijun; Zhang, Lei; Li, Mengdi; Liu, Rui; Li, Tianfang; Chen, En; Liu, Shengyun (Frontiers in Cardiovascular Medicine, 2022)
Objective This study aimed to investigate the association of serum bone turnover markers (BTMs) with metabolic syndrome components and carotid atherosclerosis in patients with type 2 diabetes mellitus (T2DM). Methods We performed a cross-sectional based study in T2DM populations. Serum BTMs including N-terminal osteocalcin (N-MID), β-cross-linked C-telopeptide of type I collagen (β-CTX), and procollagen type I N-terminal propeptide (PINP) were measured by immunoassay method. Carotid artery intima-media thickness and carotid artery plaque (CAP) were measured by B-mode ultrasound. Results The serum N-MID, PINP, and β-CTX levels significantly lower in the CAP group compared with the non-CAP group. N-MID and PINP levels were inversely associated with fasting blood glucose, HOMA-IR, CRP, eGFR, and triglycerides (all P < 0.05), whereas β-CTX levels were negatively associated with triglycerides (P < 0.05). After multiple adjustment, the odds ratios (ORs) were substantially higher for CAP with decreased N-MID level (OR = 0.958; 95% CI = 0.926–0.991; P = 0.013). However, serum levels of PINP and β-CTX were not associated with the presence of CAP. Multivariate logistic regression analysis further revealed that serum N-MID, PINP, and β-CTX levels were significantly associated with hypertriglyceridemia, whereas serum N-MID and β-CTX levels were associated with overweight/obesity risk. Conclusions These findings indicated that serum N-MID level was an independent risk factor for carotid atherosclerosis, whereas BTM levels were associated with other metabolic syndrome components in a T2DM population.